The Effect of Muscle Strength Training in the Opposite Way on Increasing the Range of Motion and Working Muscles of the Ancestral Ends of Football Players - Hawail Farhan Alkabi, Abdullah; Abdullah, Nawar (International Journal of Psychosocial Rehabilitation, 2020)
The study aimed to identify the effect of strength training in the opposite way in increasing the range of movement and working muscles of the ancestral parties of football players. The study was conducted on a sample of Diwaniyah football team consisting of (16) players and the researcher used the experimental method by (8) weeks by ( 3) Training units per week, and the time of the main part of the daily training unit ranges at a rate of (40-60) minutes. The researcher used statistical treatments in the SPSS statistical program and concluded the following:• The muscle strength exercises in the opposite way contributed to increasing the motor flexibility and working muscle strength.The most important recommendations• The necessity of making use of this study in increasing the range of movement and strengthening the working muscles of the lower extremities of football players.